The survivor - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller, 2023)
Unearthing the perfectly preserved body of a female warrior in Southeast Asia, archeologist Riley Smith and Eve Duncan seek answers about this extraordinary past life, leading Riley to make a discovery that will change history--if she can survive long enough to share it with the world.